Waste generation and management in Bangladesh: An overview - Abedin, Md Anwarul; Jahiruddin, M (Asian Journal of Medical and Biological Research, 2015)
This paper focuses on the status of solid waste generation, waste management system and waste management problems in Bangladesh. Solid waste generation is in increasing trend with the growth of urban population. The country is generating about 8000 tons of solid waste each day from the six major cities (Dhaka, Chittagong, Khulna, Rajshahi, Barisal and Sylhet), of which Dhaka city alone is contributing about 70%. Waste management system is not well organized. Efforts are underway to improve the system of waste collection, transportation, recycling, incineration and land filling. Lack of regulations/standard for waste disposal, landfill & use, lack of awareness, improper choice of technology and inadequate financial support are the major constraints for waste management in Bangladesh. Asian J. Med. Biol. Res. June 2015, 1(1): 114-120